Diagnostic study on teacher’s knowledge of educational technology at the Department of Foreign Languages of the University of El Salvador, year 2015 - Bernal de Rodriguez, Jackeline Lissette; Juárez, Wendy Guiselle; Zúniga Menjivar, Karla Iveth (2024)
This project titled: “Diagnostic study on teacher’s knowledge of educational technology at the department of foreign languages of the University of El Salvador, year 2015” aims to determine the level of educational technology knowledge professors from the Foreign Language Department of the University of El Salvador have in both contexts: inside and outside the classroom. It has been chosen because nowadays technology runs in the veins of society, in other words, the world is surrounded by technology; influencing in all life aspects, where it major influences are felt more at schools, colleges and universities. Manaly Oak (2015). In response to this statement the creation of Modern Information and Communication Technologies (ICTs) and Modern Information and Communication Technologies (ICTs) are helping to the implementation of technology in all educational levels, including universities. ICTs have been shown to be a great support for both teachers and students. The focus of this technologies is to increase teacher’s productivity and prepare professionals to live and work in an information society, where ICTs play an important role because “The implementation of technology in education should be seen only as a support tool, does not have to replace the teacher, but aims to help the student to have more elements (visual and auditory) to enrich the teachinglearning process”